NEW WORLD UTOPIA ELEMENTS IN CHRISTOPHER NOLAN'S THE DARK KNIGHT TRILOGY - Bhakti Satrio Nugroho (CrossOver, 2021)
This paper aims to analyze the representation of New World Utopia elements in one of the highest grossing movie franchises, Christopher Nolan's The Dark Knight Trilogy which consists of three movies Batman Begins (2005), The Dark Knight (2008) and The Dark Knight Rises (2012), all of them directed by Christopher Nolan and written by David S. Goyer. In this movie franchise, the depiction of American utopia elements can be seen clearly by looking at the plots, characters and other supporting data. By using Stuart Hall’s Representation Theory, this analysis explains the representation of New World utopia elements in Christopher Nolan’s The Dark Knight trilogy. The representation of these elements can be found in the form of the rule of law, beloved community, liberalism and populism. This American popular narrative consists of American values and ideologies which can be accepted not only by American audience but also worldwide audience.